Designing efficient order picking systems: The effect of real-life features on the relationship among planning problems. (May 2019) - van Gils, Teun; Caris, An; Ramaekers, Katrien; Braekers, Kris; de Koster, René B.M.
Highlights: Safety constraints induce wait times and cause additional traveling. Picker blocking (wait time) can be minimized at the expense of increased setup time. High-level storage and slow vertical travel result in extra travel and wait times. Perimeter storage, seed batching, few zones, and optimal routing performs best. Ignoring real-life features yields strongly increased order pick times of up to 30%. Abstract: This study illustrates the relevance and importance of incorporating safety constraints, picker blocking, and vertical travel due to high level storage locations when developing order picking systems (i.e., deciding on zoning, storage, batching, and routing). Results show that safety constraints induce wait times, and cause additional traveling, picker blocking and consequent wait time can be minimized at the expense of additional setup time, and slow vertical travel results in additional travel and wait times. Consequently, ignoring these real-life features causes substantial performance inefficiencies. Robust policies for organizing operations efficiently are provided, even if the system is subject to real-life features.